2021
DOI: 10.1093/jas/skab225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary macronutrient profile on apparent total tract macronutrient digestibility and fecal microbiota, fermentative metabolites, and bile acids of female dogs after spay surgery

Abstract: Obesity and estrogen reduction are known to impact the gut microbiota and gut microbial-derived metabolites in some species, but limited information is available in dogs. The aim of this study was to determine the effects of dietary macronutrient profile on apparent total tract macronutrient digestibility, fecal microbiota, and fecal metabolites of adult female dogs after spay surgery. Twenty-eight adult intact female beagles (age: 3.02 ± 0.71 yr, BW: 10.28 ± 0.77 kg; BCS: 4.98 ± 0.57) were used. After a 5-wk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…By analyzing the pH of the fresh feces of dogs, it was shown that the long-term consumption of either low-or high-energy diets caused fecal acidification, which was related to the metabolites in the feces and the composition of the gut microbiota, in several studies on canine nutrition [50][51][52][76][77][78]. Based on the above, the total SCFAs in the feces were measured in this study and were increased significantly in the Le group, especially for acetic acid and butyric acid.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the pH of the fresh feces of dogs, it was shown that the long-term consumption of either low-or high-energy diets caused fecal acidification, which was related to the metabolites in the feces and the composition of the gut microbiota, in several studies on canine nutrition [50][51][52][76][77][78]. Based on the above, the total SCFAs in the feces were measured in this study and were increased significantly in the Le group, especially for acetic acid and butyric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, microbial-derived BAs have been increasingly studied in canines ( Table 1 ). Studies in healthy dogs have characterized the microbial-derived BAs during the development of puppies [ 114 ], as well as the impact of antimicrobials [ 59 , 115 , 116 , 117 , 118 ] and diet [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ] on the BA pools of healthy dogs. Additional studies on disease states have largely focused on the context of gastrointestinal [ 52 , 64 , 127 , 128 , 129 , 130 , 131 ] and pancreatic disease [ 128 , 132 ], with additional information characterizing microbial-derived BAs in canine obesity [ 119 , 125 ], diabetes mellitus [ 113 ], and myxomatous mitral valve disease (MMVD) [ 133 ].…”
Section: Canine Microbial-derived Bile Acidsmentioning
confidence: 99%
“…Therefore, in healthy dogs, additional multi-omics studies are required to characterize collaborative BA metabolism, specifically describing canine gut microbes mechanistically responsible for BA biotransformations in health. In the following sections, the impact of antimicrobials [ 59 , 115 , 116 , 117 , 118 ] and diet [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ] on the BA pools of healthy dogs will be reviewed.…”
Section: Canine Microbial-derived Bile Acidsmentioning
confidence: 99%
See 2 more Smart Citations